Clearance or Hijack: Universal Interplay Mechanisms Between Viruses and Host Autophagy From Plants to Animals - Wu, Wenxian; Luo, Xiumei; Ren, Maozhi (Frontiers in Cellular and Infection Microbiology, 2022)
Viruses typically use host intracellular mechanisms for self-replication and establishment of infection, while hosts use a variety of defense responses to limit viral invasion. Among them, autophagy, an ancient catabolic pathway, is a powerful tool used by host cells to resist viral infection. Double-membrane vesicles called autophagosomes transport trapped viral cargo into lysosomes or vacuoles for degradation. However, in an ongoing arms race, viruses have continuously evolved to acquire a strong ability to disrupt and manipulate autophagy. In this review, we analyze animal and plant cellular autophagy antiviral defense mechanisms, and compare how animal and plant viruses evade immune responses by disrupting and manipulating host autophagy pathways to develop in directions beneficial to them. We highlight the existence of a generally versatile interaction mechanism between viruses and host autophagy in plants and animals. We hope to provide new insights and avenues for the study of plant autophagy and virus interaction through such a comparison.